Practical way of creating differential diagnoses through an expanded VITAMINSABCDEK mnemonic - Zabidi A, Zabidi Hussin (Dove Medical Press, 2016)
Having an organized, structured thinking process is critical in medicine. It is through this thinking process that enables one to go through the method of history-taking, which will eventually lead to making a definitive diagnosis and all other processes that follow. The use of mnemonic has been found to be useful for this purpose. The mnemonic VITAMINSABCDEK, is a convenient and practical way to assist in expanding the differential diagnoses and covers all possible causes of an illness. It is also easy to remember, as the vitamins whose letters are represented in this mnemonic cover the entire range of vitamins known.